Occurrence of major and trace elements in powdered milk from Argentina - Arellano, Flavia Elisa (2019)
The concentrations of major and trace elements in Argentinean commercial powdered milk samples were determined with inductively coupled plasma mass spectrometry. Also the daily intake (DI) was calculated for adults and infants. The concentrations of B, Mg, Na, K and Ca were significantly higher in skimmed milk. Cu, Mo, Fe, Mn and Zn were significantly higher in infant formula. All the DIs were below the tolerable upper intake levels. The mean As concentration (26.0 ± 8.6 ng/g) in the powdered skimmed milk samples was slightly higher than in the others. Mean Pb concentrations ranged from 4.1 ± 2.1 to 13.5 ± 8.2 ng/g. The highest mean U concentration was 7.8 ± 2.6 ng/g for whole milk. This study contributes to the knowledge of major and trace elements in powdered milk and its contribution to the diet in Argentina.